Vehicle routing and resource distribution in postdisaster humanitarian relief operations. (2nd June 2016) - Al Theeb, Nader; Murray, Chase
Abstract: After a disaster, supplies must be efficiently and equitably distributed to those in need, wounded persons must be evacuated to triage centers, and relief workers must be transported to affected areas. This complex humanitarian relief problem requires the coordination of numerous vehicles of varying capacities to transport goods, disaster victims, and volunteer workers through a network of roads, some of which may be impassable. To address this problem, a detailed mathematical programming model is presented. Owing to the complexity of this formulation, only small‐scale problem instances may be solved optimally via commercial solver software. Therefore, a new heuristic approach is proposed to solve problems of practical size within acceptable time restrictions. The performance of the heuristic is evaluated for numerous representative test instances.